Boredom in patients with acquired brain injuries during inpatient rehabilitation: a scoping review. Issue 22 (23rd October 2018) - Kenah, Katrina; Bernhardt, Julie; Cumming, Toby; Spratt, Neil; Luker, Julie; Janssen, Heidi
Abstract: Purpose: Boredom may impede engagement in inpatient rehabilitation following an acquired brain injury. This review aimed to: (1) describe the experience and (2) quantify the incidence of boredom; (3) identify measurement tools used to quantify boredom; (4) summarize factors contributing to boredom, and (5) outline evidence-based interventions shown to reduce boredom during inpatient rehabilitation. Methods: Two researchers independently screened publications retrieved from electronic database searches. Publications presenting patient, carer or staff data relating to boredom in inpatients with acquired brain injuries were included. Results: Two thousand four hundred and ninety-nine references were retrieved, 88 full texts were reviewed, with 24 studies included. The majority of studies reported qualitative data indicating boredom to be a common experience of patients with acquired brain injuries ( n  = 14 studies +1 review). The incidence of boredom post acquired brain injury is unknown. Personal and organizational factors and the physical environment may contribute to boredom ( n  = 11 studies +2 reviews). Qualitative work ( n  = 9 studies) indicates that use of the creative-arts or exposure to environmental enrichment may help alleviate boredom in patients with acquired brain injuries during inpatient rehabilitation. Conclusion: Further mixed-methods research is required to establish the incidence of and contributing factors to boredom in patients with acquired brain injuries undergoing rehabilitation. Understanding this will help inform future research aimed at improving patient engagement in inpatient rehabilitation. Implications for rehabilitation: Boredom is commonly reported by hospitalised patients with ABI to negatively affect their rehabilitation yet the scope of the problem has not been measured. Boredom is a complex phenomenon, likely influenced by a number of personal and environmental factors that are not fully understood in this population. Through a better understanding of boredom, interventions may be developed to improve patient engagement in inpatient rehabilitation programs.